Ferromagnetic to spin glass cross over in (La,Tb)(2/3)Ca1/3MnO3 - Sankar, C. Raj; Vijayanand, S.; Joy, Pattayil Alias (Solid State Sciences, 2009)
In the series La2/3-xTbxCa1/3MnO3, it is known that the compositions are ferromagnetic for smaller values of x and show spin glass characteristics at larger values of x. Our studies on the magnetic properties of various compositions in the La2/3-xTbxCa1/3MnO3 series show that the cross over from ferromagnetic to spin glass region takes place above x approximate to 1/8. Also, a low temperature anomaly at 30 K, observed in the ac susceptibility curves, disappears for compositions above this critical value of x. A mixed phase region coexists in the narrow compositional range 0.1 <= x <= 0.125, indicating that the ferromagnetic to spin glass cross over is not abrupt. (C) 2008 Elsevier Masson SAS. All rights reserved.
Keywords: Ferromagnetism; Magnetic clusters; Manganites; perovskite; Spin glass

Defect induced modification of structural, topographical and magnetic properties of zinc ferrite thin films by swift heavy ion irradiation - Raghavan, Lisha; Joy, P. A.; Vijaykumar, B. Varma; Ramanujan, R. V.; Anantharaman, M. R. (Nuclear Instruments & Methods In Physics Research Section B-Beam Interactions With Materials And Atoms, 2017)
Swift heavy ion irradiation provides unique ways to modify physical and chemical properties of materials. In ferrites, the magnetic properties can change significantly as a result of swift heavy ion irradiation. Zinc ferrite is an antiferromagnet with a Neel temperature of 10 K and exhibits anomalous magnetic properties in the nano regime. Ion irradiation can cause amorphisation of zinc ferrite thin films; thus the role of crystallinity on magnetic properties can be examined. The influence of surface topography in these thin films can also be studied. Zinc ferrite thin films, of thickness 320 nm, prepared by RF sputtering were irradiated with 100 MeV Ag ions. Structural characterization showed amorphisation and subsequent reduction in particle size. The change in magnetic properties due to irradiation was correlated with structural and topographical effects of ion irradiation. A rough estimation of ion track radius is done from the magnetic studies. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Spin glass; Swift heavy ion; Zinc Ferrite